Advanced wireless communications : - Glisic, Savo G. (Wiley, 2007)
This book provides a comparative study of enabling technologies for 4G. This second edition has been revised and updated and now includes additional information on the components of common air interface, including the area of space time coding , multicarrier modulation especially OFDM, MIMO, cognitive radio and cooperative transmission.